Effects of food prices on poverty: The case of Paraguay, a food exporter and a non-fully urbanized country - Santiago Garriga; María Ana Lugo; Jorge Puig (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2018)
A vast proportion of households in developing countries like Paraguay are both consumers and producers of food, and thus the effects of food price fluctuations on welfare are not obvious. Historically, the agricultural sector in Paraguay has played a key role in economic development and has contributed significantly, and increasingly, to economic growth. In recent years, sharp movements in commodity prices have been added to the inherent volatility of the sector linked to climate conditions. In this work, we use the 2011/12 expenditure and income survey, as well as monthly price data for 127 food items for the period 2007/15, to simulate the effect of a potential hike in food prices on welfare. Our main results suggest that the expenditure effect is negative and regressive everywhere, but larger in rural than urban areas. The income effect is positive and progressive in rural areas and negligible in urban ones. Therefore, we find that the potential overall impact of an unexpected increase in food prices in Paraguay is a very flat U-shaped curve. We conclude with a simple exercise where we simulate a policy response in order to help those affected by the initial increase in food prices.
Keywords: D31; I38; Q12; 330; foodprices; distribution; poverty; policy response; Paraguay